2021
DOI: 10.3390/pharmaceutics13122055
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-Based Drug Delivery Strategies to Repair the Mitochondrial Function in Neuroinflammatory and Neurodegenerative Diseases

Abstract: Mitochondria are vital organelles in eukaryotic cells that control diverse physiological processes related to energy production, calcium homeostasis, the generation of reactive oxygen species, and cell death. Several studies have demonstrated that structural and functional mitochondrial disturbances are involved in the development of different neuroinflammatory (NI) and neurodegenerative (ND) diseases (NI&NDDs) such as multiple sclerosis, Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 381 publications
(469 reference statements)
0
5
0
Order By: Relevance
“…However, in podocytes DRP1 phosphorylation at Ser637/656 promotes mitochondrial fission due to high glucose conditions, 9,35 and Ser600 phosphorylation by PKA decreases DRP1 GTPase activity 36 . In a study published in 2021, DRP1 phosphorylation at Ser637 was shown to promote subsequent Ser616 phosphorylation, and only blocking downstream Ser616 phosphorylation leads to mitochondrial elongation rather than fission 37 . In mouse embryonic fibroblasts, phosphorylation at both sites is essential for maximal fission, indicating that phosphorylation at Ser637 promotes fission or fusion and this function depends on Ser616 phosphorylation status 37 .…”
Section: Mitochondrial Dynamics In Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in podocytes DRP1 phosphorylation at Ser637/656 promotes mitochondrial fission due to high glucose conditions, 9,35 and Ser600 phosphorylation by PKA decreases DRP1 GTPase activity 36 . In a study published in 2021, DRP1 phosphorylation at Ser637 was shown to promote subsequent Ser616 phosphorylation, and only blocking downstream Ser616 phosphorylation leads to mitochondrial elongation rather than fission 37 . In mouse embryonic fibroblasts, phosphorylation at both sites is essential for maximal fission, indicating that phosphorylation at Ser637 promotes fission or fusion and this function depends on Ser616 phosphorylation status 37 .…”
Section: Mitochondrial Dynamics In Healthmentioning
confidence: 99%
“… 36 In a study published in 2021, DRP1 phosphorylation at Ser637 was shown to promote subsequent Ser616 phosphorylation, and only blocking downstream Ser616 phosphorylation leads to mitochondrial elongation rather than fission. 37 In mouse embryonic fibroblasts, phosphorylation at both sites is essential for maximal fission, indicating that phosphorylation at Ser637 promotes fission or fusion and this function depends on Ser616 phosphorylation status. 37 SUMO1, SUMO2, or SUMO3 have opposite effects on DRP1 activity.…”
Section: Mitochondrial Dynamics In Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…MS is an autoimmune disease which is not fully understood, likely has multiple distinct causes, and is not considered a genetic mitochondrial disease; however, in MS occurs much more often with LHON than would occur by chance in Harding's syndrome, and in this situation the MS symptoms can be putatively causally linked to the mitochondrial defect driving the LHON pathology [39,40]. MS has been causally linked to inflammation, while evidence increasingly supports a role for mitochondrial dysfunction [41][42][43]. Harding's syndrome provides an example of a disease clearly linked to both mitochondrial defects and inflammation.…”
Section: Evidence For Immune Involvement In the Pathogenesis Of Mitoc...mentioning
confidence: 99%
“…To treat primary mitochondrial diseases, gene therapy based on ectopic expression is still the first choice; however, the application of viral vectors in live animals to correct any gene mutation still has the following significant problems: High cost (390,(412)(413)(414)(415), carcinogenicity and immunogenicity. Non-viral vector-mediated in situ mitochondrial gene therapy may be a promising approach to overcome the bottleneck of existing gene therapy LHON, such as liposome-based nanoparticles, which require further investigation (416)(417)(418)(419)(420)(421).…”
Section: Mitochondrialmentioning
confidence: 99%